2015
DOI: 10.1016/j.fertnstert.2015.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Maternal microbiome and pregnancy outcomes

Abstract: Alterations of the human microbiome are a known characteristic of various inflammatory disease states and have been linked to spontaneous preterm birth and other adverse pregnancy outcomes. Recent advances in metagenomic research have proven that the placenta harbors its own rich diverse microbiome, even in clinically healthy pregnancies, and preterm birth may be a result of hematogenous infection rather than exclusively ascending infection as previously hypothesized. In this review, we describe the microbiome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(106 citation statements)
references
References 67 publications
(124 reference statements)
2
92
0
12
Order By: Relevance
“…Aagaard et al, however, suggested that the stability of the vaginal microbiome in pregnancy provides an adaptive benefit to reproductive health . According to Fox and Eichelberger, at the end of pregnancy, the composition of the vaginal microbiota becomes more similar to that of non‐pregnant women. On the other hand, DiGiulio et al reported significant differences in the composition of the vaginal microbiota in the post‐partum period but no changes with advancing gestational age.…”
Section: The Vaginal Microbiome During Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Aagaard et al, however, suggested that the stability of the vaginal microbiome in pregnancy provides an adaptive benefit to reproductive health . According to Fox and Eichelberger, at the end of pregnancy, the composition of the vaginal microbiota becomes more similar to that of non‐pregnant women. On the other hand, DiGiulio et al reported significant differences in the composition of the vaginal microbiota in the post‐partum period but no changes with advancing gestational age.…”
Section: The Vaginal Microbiome During Pregnancymentioning
confidence: 99%
“…Some experimental studies have found that the microbial community detected in amniotic fluid and placental samples may have originated in the oral cavity . Other investigators have shown an association between periodontal disease and PTB . Doyle et al analyzed placental tissue samples from 1390 Malawi women using 16S rRNA gene sequencing.…”
Section: Microbiome and Obstetric Disordersmentioning
confidence: 99%
“…During pregnancy, the maternal body undergoes radical physiological fluctuations in hormones and immune status [Fox and Eichelberger, 2015]. Recent studies have found that these changes are concurrent with alterations in the maternal gut microbiome, with significant shifts occurring from the first to the third trimester [Koren et al, 2012].…”
Section: Maternal Microbiome During Pregnancymentioning
confidence: 99%
“…These reciprocal relationships include the direct induction of both maternal and neonatal physiological changes so that ecological relationships within varying tissues are changed. Crucially, since this process begins before birth and then continues thereafter, it is not surprising that changes in the maternal microbiome are now being linked to a variety of differing pregnancy outcomes and pre-term birth (71). …”
Section: The Impact Of the Microbiome On Developmentmentioning
confidence: 99%